Food, Media and Contemporary Culture
XII, 274 p.
Keywords: Food, Media and Contemporary Culture is designed to interrogate the cultural fascination with food as the focus of a growing number of visual texts that reveal the deep, psychological relationship that each of us has with rituals of preparing, presenting and consuming food and images of food.